Radiologic Findings of Ductal Carcinoma in Situ Arising Within a Juvenile Fibroadenoma: Mammographic, Sonographic and Dynamic Contrast-Enhanced Breast MRI Features - Park, Eun Kyung (Iran J Radiol, 2015)
Juvenile fibroadenoma is an uncommon histologic variant of fibroadenoma that frequently shows a remarkable and rapid growth. The development of a carcinoma within a fibroadenoma, either in situ or invasive, is a rare condition. We encountered a 36-year-old woman with a palpable mass in the right breast. The radiologic findings were indicative of a fibroadenoma in the breast. Sonographic guided biopsy using a 14G core needle revealed the presence of ductal carcinoma in situ (DCIS) within the juvenile fibroadenoma. Focal excision was performed and the patient underwent radiation therapy in the right breast after surgery.